2006
DOI: 10.1007/s11010-006-9239-y
|View full text |Cite
|
Sign up to set email alerts
|

The roles of translation initiation regulation in ultraviolet light-induced apoptosis

Abstract: Ultraviolet light (UV) inhibits translation initiation through activation of kinases that phosphorylate the alpha-subunit of eukaryotic initiation factor 2 (eIF2alpha). Two eIF2alpha kinases, PERK and GCN2, are known to phosphorylate the Serine-51 of eIF2alpha in response to UV-irradiation. In this report, we present evidence that phosphorylation of eIF2alpha plays a role in UV-induced apoptosis. Our data show that wild-type mouse embryo fibroblasts (MEF(s/s)) are less sensitive to UV-induced apoptosis than ME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 44 publications
2
17
0
Order By: Relevance
“…We also observed that, in PERK knockdown G401 cells and mPERK knockdown MEF cells, similar to the findings in HeLa cells, SubAB-induced caspase-7 activation was inhibited. There are cases in which PERK activation promotes or protects against ER stress-induced apoptosis (11,19,22,36). These studies imply that PERK plays different roles in regulation of cell proliferation or apoptosis, depending on the cell type or species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also observed that, in PERK knockdown G401 cells and mPERK knockdown MEF cells, similar to the findings in HeLa cells, SubAB-induced caspase-7 activation was inhibited. There are cases in which PERK activation promotes or protects against ER stress-induced apoptosis (11,19,22,36). These studies imply that PERK plays different roles in regulation of cell proliferation or apoptosis, depending on the cell type or species.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous data showed that after treatment of cells with SubAB, protein synthesis was transiently suppressed for 2 h and then moderately recovered; these events were probably regulated by a pathway downstream of eIF2␣ phosphorylation (30). A recent study showed that eIF2␣ kinases may mediate UV light-induced apoptosis via eIF2␣-dependent or -independent signaling pathways (36). In contrast, studies of ␤-amyloid (A␤)-mediated cell death in SK-N-SH human neuroblastoma cells demonstrated that maintaining levels of phosphorylation of eIF2␣ inhibited cell death (22).…”
Section: Figmentioning
confidence: 99%
“…Although the roles of PERK and GCN2 in UV-induced translation inhibition and downstream signal transduction have been previously elucidated (2,4,28), their key activators have not been identified. We now demonstrate that UVB-induced translational inhibition in cultured human skin cells is, at least partially, mediated by NOS-catalyzed NO ⅐ production in combination with superoxide production.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have demonstrated the role played by GCN2 in other cellular responses, such as sensitivity to RNA viral infection 5 or T-cell differentiation. 6 Although GCN2 is typically activated by amino acid deprivation, UV exposure 7,8 or high levels of urea 9 can also lead to GCN2 activation. These data suggest that GCN2 could act as a key regulator to the cellular response under stress conditions.…”
mentioning
confidence: 99%